Вплив регуляторів росту рослин на формування продуктивності сої в Центрі України - Мащенко, Євген Олександрович; Mashchenko, Yevhen (ЦНТУ, 2024)
В даній випускній кваліфікаційній роботі вивчено ефективність застосування регуляторів росту рослин у технології вирощування сої в умовах Центру України. Мета досліджень - вивчити ефективність регуляторів росту при вирощуванні сої в умовах Центру України. Встановлено, що найбільш ефективним в умовах Центру України при вирощуванні сої сорту Кентуккі є дворазове застосування регулятору росту рослин Stimulate для обробки насіння перед сівбою та в подальшому обприскування посівів культури під час вегетації. This final qualification work studies the effectiveness of using plant growth regulators in soybean growing technology in the conditions of the Center of Ukraine. The purpose of the research is to study the effectiveness of growth regulators in soybean growing in the conditions of the Center of Ukraine. It was found that the most effective in the conditions of the Center of Ukraine when growing Kentucky soybeans is the double application of the Stimulate plant growth regulator for seed treatment before sowing and subsequent spraying of crops during the growing season.
Influence of plant growth regulators on the formation of soybean productivity in the Centre of Ukraine
Keywords: соя; регулятори росту рослин; економічна ефективність; soybean; plant growth regulators; economic efficiency